"Same, same but different": The optimal viewing position effect in developmental dyslexia, developmental coordination disorder and comorbid disorders. (2nd June 2021) - Bellocchi, Stéphanie; Ducrot, Stéphanie
Abstract : The optimal viewing position (OVP) effect indicates that words are identified most quickly when the eyes fixate near the word centre in alphabetic languages. In two studies, we tested OVP in typically developing readers and children with developmental dyslexia (DD), developmental coordination disorder (DCD) and with both disorders (DD + DCD), using a variable‐viewing‐position technique. Study 1 showed that typically developing readers had developed highly automatized procedures of left‐to‐right attentional scanning resulting in an inverted J ‐shape VP curve comparable to what is observed in adult readers and that dyslexics showed non‐prototypical one. In Study 2, we observed more typical procedures of left‐to‐right attentional scanning in children with DCD, isolated or comorbid, compared to DD. Moreover, given the absence of significant group differences between children with DD + DCD and children with isolated DD or DCD, our results reinforce the idea that the comorbid condition does not add to the severity of OVP anomalies. We then concluded that OVP atypicalities are specific to children with DD. Finally, we discussed the usefulness of the OVP effect as a clinical tool to identify possible OVP atypicalities that could be specific of some neurodevelopmental disorders (i.e., DD, DCD or DCD + DD).